Electromechanical Battery EMB Mass Minimization taking into Account its Electrical Machines Rotor Energy - Podgornovs, Andrejs; Sipovichs, Antons (Electrical, Control and Communication Engineering, 2014)
In this paper the electromechanical battery (EMB) with synchronous machine is described. Theoretically, if electrical machines rotor stored energy is known, it is possible to reduce the flywheel mass of electromechanical battery. For example, the efficiency of energy recovery (kilowatt-hours out versus kilowatthours in) in nowadays appliances exceeds 95 % which is considerably better than of any electrochemical battery, such as lead-acid battery. For the rotor stored energy amount calculation, it is necessary to find all geometrical dimensions of the electrical machine. To achieve this goal the iterative calculation method was used. Electromechanical battery mass was analyzed as a discharge process rotation speed function. Taking into account the rotor stored energy, we can increase the minimum rotation speed thus reducing the electrical machine mass and increasing the flywheel mass, which provides EMB cost reduction. Additionally, the possibilities of using numerical approximation calculations of magnetization curves are discussed. Each iteration of numerical application necessary for the method for rapid calculation is essential when calculating the field problems. Nowadays there are a lot of computer added design programs for electromagnetic field calculation in different types of applications, electrical machines and apparatus. For the electromagnetic field calculation process some more commonly used magnetization curve approximation methods are described, and the machine calculation time is tested for different numbers of calculations.